The use of the wide-awake local anesthesia no tourniquet technique in foot and ankle injuries. Issue 5 (July 2021) - Bilgetekin, Yenel Gürkan; Kuzucu, Yakup; Öztürk, Alper; Yüksel, Sinan; Atilla, Halis Atıl; Ersan, Önder
Highlights: WALANT technique can be used for the surgical treatment of several foot and ankle injuries with satisfying pain and anxiety during the operation. Common ankle fractures and tendon injuries can be operated with WALANT anesthesia. WALANT provides a short length of hospital stay for patients with foot and ankle injuries. Abstract: Purpose: Although the wide-awake anesthesia no tourniquet (WALANT) technique has demonstrated high efficacy, safety, patient satisfaction, and cost-effectiveness in hand surgery, there are limited data on its use in foot and ankle surgery. This study aimed to evaluate the efficacy of the WALANT technique in selected foot and ankle injuries in terms of intra- and post-operative characteristics. Material and methods: Patients with foot and ankle injuries who underwent surgery with the WALANT technique were evaluated in this retrospective study. A total of 31 patients (22 male/9 female) with a mean age of 40 ± 16 years were evaluated for the type of injury, underlying comorbidities, American Society of Anesthesiologists Classification (ASA) score, intraoperative visual analog pain (VAS) and anxiety (VAS-A) scores, duration of operation, complications, need for intensive care and duration of hospitalization. Results: There were 15 patients with medial malleolus fracture, 5 with lateral malleolus fracture, 5 with Achilles tendon ruptures, 2 with proximal phalangeal fracture, and 1 with Lisfranc injury, medial malleolus + syndesmotic injury, deltoid ligament + syndesmotic injury and fifth metatarsal fracture. ASA I–II score was determined in 27 patients and ASA III score in 4. The mean operation time was 36.6 ± 7 min, and the mean length of hospital stay was 8.3 ± 6.1 h. The median VAS pain score was 1 (range, 0–4), the median VAS-A score was 1 (range, 0–3) and no patient needed further anesthetics during the operation. No patient needed intensive care unit stay and no complications were observed in any patient. Conclusion: The WALANT technique was seen to provide satisfactory anxiety and pain scores, acceptable complications, and a short length of hospital stay in patients with foot and ankle injuries. Simple foot and ankle injuries can be managed successfully with this technique through adequate hemostasis without a tourniquet. Level of evidence: Level III.